Psychometric Scale Development for the Measurement of Entrepreneurial Behaviour of Vegetable Growers - Vineeta; Ajay Kumar Prusty; Chitrasena Padhy; Rabindra Kumar Raj; Soumik Ray (Indian Journal of Extension Education, 2026)
The study conducted in 2025 developed and standardised a valid and dependable psychometric scale to assess vegetable growers’ entrepreneurial behaviour. An initial pool of 76 statements was produced using Likert’s summated rating approach. Following editing, 86 experts tested the statements for relevancy using mean relevancy score, relevancy weightage, and relevancy percentage. The crucial ratio (t-value) method was used to analyse the replies of 60 vegetable growers who were chosen from non-sample locations. 33 statements were ultimately chosen to be included in the scale based on discrimination power. The split- half approach was used to determine the instrument’s reliability, and the results showed excellent internal consistency and elevated levels of Cronbach’s alpha value (0.891 and 0.955) and a satisfactory Guttman Split- half Coefficient (0.720). Expert judgement was used to guarantee content reliability and validity. Researchers, extension specialists, and legislators should find the developed scale to be a helpful tool for evaluating entrepreneurial behaviour and creating need-based interventions to improve the entrepreneurial skills of vegetable growers.